Yeni Ekonominin Makroekonomi Üzerindeki Etkileri - Erdil Şahin, Begüm; Ayhan, Damla (İstanbul Kültür Üniversitesi / İktisadi ve İdari Bilimler Fakültesi / İktisat Bölümü, 2014)
World economics is going through a structural reform period due to the developments on the information and communication technologies and impacts of globalization on business. New Economy has emerged as a consequence of these two facts and is characterized as a more advanced economic structure than today’s economy. The path for increasing efficiency, development of qualified workforce, steady growth, getting advantage from international competition and creating sustainable development is going through benefiting from knowledge and communication technologies and using knowledge economy. In this study, the new economy concept, its basic characteristics and the importance of the new economy and technology are defined and through its impact on macroeconomics, the impacts on economic growth, efficiency, employment, external trade, income allocation and welfare are evaluated.
Keywords: Yeni Ekonomi; Ekonomik Büyüme; Verimlilik; İstihdam; Makroekonomi; New Economy; Economic Growth; Efficiency; Employment; Macroeconomics